The Water-Energy-Food Nexus in the Mediterranean Region in a scenario of polycrisis - Quagliarotti, Desirée Ada Ludmilla (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Multiple global crises, including climate change, the COVID-19 pandemic, and Russia’s war on Ukraine, have recently linked together in ways that are significant in scope, devastating in effect, but still poorly understood, triggering what experts call a real polycrisis. In particular, climate change and the Ukraine conflict, acting together, are increasingly putting at risk the availability and access to fundamental resources to human survival and well-being: water, energy and food. The Mediterranean region could be considered both a water, energy and food (WEF) nexus and a climate change ‘hotspot’. Since Russia and Ukraine are central players in global commodity markets, the ongoing war and accompanying sanctions are dramatically unsettling energy and food markets, with ripple effects likely to extend well into 2024. The new global systemic risks call for a paradigm shift by adopting measures to reduce exposure and strengthen resilience turning the conventional WEF nexus into a virtuous circle. To face these challenges, three main actions are identified: mainstreaming climate change into the WEF nexus; decouple water, energy and food production from fossil fuel; develop sustainable WEF intra-regional and regional cooperation/integration models based on the principle of comparative advantages. To illustrate these mechanisms the cascading impacts of interactions between the Ukraine-Russia war and climate change on the WEF nexus in the Mediterranean countries are illustrate.